Hepatotoxicity of decabromodiphenyl ethane (DBDPE) and decabromodiphenyl ether (BDE-209) in 28-day exposed Sprague-Dawley rats - Sun, Yanmin; Wang, Yuwei; Liang, Baolu; Chen, Tian; Zheng, Dan; Zhao, Xuezhen; Jing, Li; Zhou, Xianqing; Sun, Zhiwei; Shi, Zhixiong (The Science of the total environment, 2020)
Decabromodiphenyl ether (BDE-209) and its substitute decabromodiphenyl ethane (DBDPE) are heavily used in various industrial products as flame retardant. They have been found to be persistent in the environment and have adverse health effects in humans. Although some former studies have reported toxic effects of BDE-209, the study of DBDPE's toxic effects is still in its infancy, and the effects of DBDPE on hepatotoxicity are also unclear. This study aimed to evaluate and compare the hepatotoxicity induced by BDE-209 and DBDPE using a rat model. Sprague-Dawley rats were administered DBDPE or BDE-209 (5, 50, 500 mg/kg bodyweight) intragastrically once a day for 28 days. Twenty-four hours after the end of treatment, the rats were sacrificed, and body liver weight, blood biochemical parameters, liver pathology, oxidative stress, inflammation, pregnane X receptor (PXR), constitutive androstane receptor (CAR), and changes in cytochrome P450 (CYP3A) enzymes were measured. Our results showed that both BDE-209 and DBDPE could cause liver morphological changes, induce oxidative stress, increase γ-glutamyl transferase and glucose levels in serum, and down-regulate PXR, CAR, and CYP3A expression. In addition, BDE-209 was found to increase liver weight and the ratio of liver/body weight, lead to elevated total bilirubin and indirect bilirubin levels in serum, and induce inflammation. The present study indicated that BDE-209 and DBDPE may interfere with normal metabolism in rats through oxidative stress and inflammation, which inhibit PXR and CAR to induce the expression of CYP3A enzymes, and finally produce hepatotoxic effects and cause liver damage in rats. Comparatively, our results show that the damage caused by BDE-209 was more serious than that caused by DBDPE. [Display omitted] •Hepatotoxicity induced by BDE-209 and DBDPE in rats was studied and compared.•Both BDE-209 and DBDPE can cause liver damage whereas DBDPE is less toxic.•BDE-209 and DBDPE may interfere metabolism in rats through oxidative stress and inflammation.